Biotechnological Evolution of siRNA Molecules: From Bench Tool to the Refined Drug - Danielle de Brito e Cunha; Ana Beatriz Teixeira Frederico; Tamiris Azamor; Juliana Gil Melgaço; Patricia Cristina da Costa Neves; Ana Paula Dinis Ano Bom; Tatiana Martins Tilli; Sotiris Missailidis (MDPI AG, 2022)
The depth and versatility of siRNA technologies enable their use in disease targets that are undruggable by small molecules or that seek to achieve a refined turn-off of the genes for any therapeutic area. Major extracellular barriers are enzymatic degradation of siRNAs by serum endonucleases and RNAases, renal clearance of the siRNA delivery system, the impermeability of biological membranes for siRNA, activation of the immune system, plasma protein sequestration, and capillary endothelium crossing. To overcome the intrinsic difficulties of the use of siRNA molecules, therapeutic applications require nanometric delivery carriers aiming to protect double-strands and deliver molecules to target cells. This review discusses the history of siRNAs, siRNA design, and delivery strategies, with a focus on progress made regarding siRNA molecules in clinical trials and how siRNA has become a valuable asset for biopharmaceutical companies.